Cortical Substrate of Supraspinal Fatigue following Exhaustive Aerobic Exercise Localizes to a Large Cluster in the Anterior Premotor Cortex - Herath, Priyantha; Carmichael, Martin; Murphy, Angela; Bonilha, Leonardo; Newman-Norlund, Roger; Rorden, Chris; Davis, Mark (Frontiers in Neurology, 2017)
Strenuous exercise leads to a progressive reduction in the performance of voluntary physical exercise. This is due to a process described as fatigue and is defined as the failure to maintain the required or expected power output. While some of this is muscular in origin, there are data suggestive of how fatigue is modulated by cortical signals, leading to a concept of central fatigue. The previously reported fatigue-induced changes in cortical activity may have been due to blood oxygen-dependent (BOLD) signal drift and/or neural habituation alone. We implemented a functional magnetic resonance imaging paradigm to effectively isolate brain areas responsible for central (supraspinal) fatigue following exercise. Our data identify a large cluster that includes dominant the anterior ventral premotor cortex (aPMv), the insula and postcentral gyrus as critical nodes in the brain network where supraspinal fatigue might have their functional neural imprints. Findings here show that activity in the ipsilateral aPMv and the adjacent areas in the premotor cortex correlates with both localized fatigue (fatigue specific hand grip contraction), and generalized full body exhaustive fatigue. In addition, from a methodological standpoint, we have also shown that the effects of BOLD signal drift can be modeled and removed to arrive at specific brain activity patterns in our experiments. Once the loci of central fatigue are isolated in this way, treatments aimed at modulating activity in these premotor areas may reduce exercise-induced fatigue and perhaps also benefit various clinical conditions in which fatigue is a major symptom.